2016
DOI: 10.2217/whe.15.78
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Embolization for Heavy Menstrual Bleeding

Abstract: Uterine artery embolization (UAE) as a treatment option for fibroids was first reported by Ravina in 1995. Although rapidly adopted by enthusiasts, many were skeptical and its introduction varied widely across the globe. It was not until randomized controlled trials and registries were published and national guidance statements issued that UAE was accepted as a safe and proven treatment for fibroids. The technique is now established as one of the treatment options to be discussed with patients as an alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Although rapidly adopted by enthusiasts, the introduction of UAE has varied widely across the globe ( Moss and Christies, 2016 ). This technique was first used in 1995 ( Ravina et al ., 1995 ) to treat uterine fibroids in women wishing to preserve their uterus.…”
Section: Alternatives To Surgical Interventionmentioning
confidence: 99%
“…Although rapidly adopted by enthusiasts, the introduction of UAE has varied widely across the globe ( Moss and Christies, 2016 ). This technique was first used in 1995 ( Ravina et al ., 1995 ) to treat uterine fibroids in women wishing to preserve their uterus.…”
Section: Alternatives To Surgical Interventionmentioning
confidence: 99%
“…However, these patients did not appear to experience hot flushes, night sweats, insomnia, anxiety and other perimenopausal symptoms. In addition, studies have shown that hysteromyomectomy does not affect the blood supply of ovaries [15], and has less impact on accessories, so the short-term and long-term impact on ovarian function is not obvious. Our results also showed that AFC and AMH did not change significantly in this group within 18 months after operation, that is, ovarian function was not significantly affected.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of UAE into routine clinical practice is widely endorsed and its role in heavy menstrual bleeding has been investigated recently. [13] Previously, a local study by Prollius et al…”
Section: Researchmentioning
confidence: 99%
“…Incorporation of UAE into routine clinical practice is widely endorsed and its role in heavy menstrual bleeding has been investigated recently. [13] Previously, a local study by Prollius et al[10] reported a mean reduction in uterine volume of 188 cm 3 in 51 women on follow-up at 12 months. There are limited local data on the long-term effect of UAE on symptomatic fibroid volume reduction using follow-up ultrasound imaging.…”
mentioning
confidence: 99%